What jobs should a public job guarantee provide? Lessons from Hyman P. Minsky - Daniel Haim (Levy Economics Institute of Bard College, 2021)
The job guarantee is a viable policy option for tackling both unemployment and underemployment. Hyman P. Minsky was one of the seminal writers on this subject. The first part of this working paper provides a survey of Minsky's writings to identify what kind of jobs he had in mind when recommending employer-of-last-resort policies. Minsky favored: (1) jobs increasing socially useful output, providing all of society better public services and goods; (2) jobs guaranteed by the public sector on a project-by-project basis at a minimum wage; (3) jobs in the places where people need them; and (4) jobs taking the people that need them as they are. The second part of the paper suggests policy recommendations for today's economy. As long as the COVID-19 pandemic still rages on, a targeted public job guarantee program can assist in the social provisioning and distribution of food, shelter, and medical services. After the pandemic, a public job guarantee can reduce poverty and inequality, and bring about a more democratic, sustainable, and socially cohesive economic system.
Keywords: B31; E24; E61; H41; H53; I38; J21; J45; J68; 330; Job Guarantee; Public Service Employment; Employer of Last Resort (ELR); Unemployment; Full Employment; Minsky; Policy Design; COVID-19